ANALISIS PENGARUH PELATIHAN DAN JAM KERJA TERHADAP KINERJA KARYAWAN PNM MEKAAR SYARIAH DI KOTA DEPOK - Rizky Fadhila; Izzani Ulfi (UIN Mataram, 2021)
Human resource is an asset for any institution including Islamic financial institutions. Their performance would also determine the success of the institution. Therefore, this study aims to check the influence of training and working hours variables on the performance of PNM Mekaar Syariah employees Depok. Primary data has been collected through questionnaires. Purposive sampling technique has been used and 67 employees PNM Mekaar Syariah Depok have participated in the questionnaires. For data analysis, Multiple Regression Analysis is employed and processed using SPSS 25. The result shows that based on the t-test, both training and working hours variables do not affect the performance of employees. However, it is found that based on the F test, training variables and working hours are simultaneously affect the performance of PNM Mekaar Syariah employees in Depok City.